PEMANFAATAN APLIKASI MOBILE LIBRARY IPUSNAS PADA PERPUSTAKAAN - Putri, Kadek Taristya Pradnyan; Haryanti, Ni Putu Premierita; Ginting, Richard Togaranta (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2022)
Along with the times, library-comparison to provide a reliable source of information. In the era of globalization, people's mindsets continue to develop which has an impact on how to find sources of information where users search for internet information sources with the help of smartphones, it is easy to find information about the spread of hoax news among the public. Therefore, libraries need to innovate by creating digital library services that can be accessed via smartphones, commonly known as mobile libraries. The iPusnas application is a digital library application that helps users find information without being hindered by distance and time. The iPusnas application has interesting features and collections that make this application superior.